IMPLEMENTATION OF CONSORTIUM BACTERIES OF Bacillus cereus ISOLATED FROM SEA AS PROTEIN SOURCE FOR PRO COFFEE BEVERAGE - Zevira, Bella Permata; Feliatra, Feli; Batubara, Ummi Mardhiah (Asian Journal of Aquatic Sciences, 2024)
Pro coffee is a fermented beverage using Bacillus cereus bacterial consortium with single-cell protein. This study aims to determine the best composition of the B. cereus consortium bacteria mixture in organoleptic aspects that panelists most prefer and the effect of adding B. cereus consortium bacteria on proximate analysis and pro coffee flavor. Organoleptic testing of probiotic coffee was conducted on 20 panelists, then continued with proximate analysis of pro coffee. The composition with the best organoleptic flavor is obtained in code D, with the treatment of adding 5% bacterial consortium B. cereus for 15 days. The analysis of taste obtained has a value of 0.000 <0.05, and the study results show that the significance value is smaller than the significance level. Hence, the treatment results give the effect of adding bacterial consortium to pro-coffee. The addition of bacterial consortium B. cereus to probiotic coffee, in the form of moisture, ash, protein, fat, and carbohydrate content, is 0.000 <0.05. The analysis results show that the significance value is greater than the significance level, so the treatment results do not give the effect of adding bacterial consortium to pro coffee